Discussion of "Phantom Penis: Extrapolating Neuroscience and Employing Imagination for Trans Male Embodiment". Issue 4 (1st October 2020) - Case, Laura
ABSTRACT: Straayer synthesizes literary and scientific discourse on the trans phantom penis, presenting a compelling argument for greater roles of diversity and imagination in its conceptualization. In this response I first introduce a recently uncovered historical reference to phantom genitals that precedes those discussed by Straayer and that extends the trans phantom penis beyond the Western canon. I next compare what is known about the sensory and cortical origins of the trans phantom penis with the sparse scientific research on phantom breasts and vaginas. Finally, I elaborate on Straayer's suggestion that sociology be considered in research on trans phantom body parts, illustrating the role of social factors both in phantom body parts and in scientific understandings of sex and gender.